Allogeneic peripheral blood stem-cell compared with bone marrow transplantation in the management of hematologic malignancies: an individual patient data meta-analysis of nine randomized trials. - Stem Cell Trialists' Collaborative Group (2005)
PURPOSE: Considerable uncertainty exists regarding relative effects of allogeneic peripheral blood stem cells transplantation (PBSCT) versus bone marrow transplantation (BMT) on outcomes of patients with hematologic malignancies. PATIENTS AND METHODS: To provide the totality of research evidence related to the effects of PBSCT versus BMT, we conducted an individual-patient data meta-analysis using data from nine randomized trials enrolling 1,111 adult patients. RESULTS: Compared with BMT, PBSCT led to faster neutrophil (odds ratio [OR] = 0.31; 95% CI, 0.25 to 0.38; P < .00001) and platelet engraftment (OR = 0.52; 95% CI, 0.44 to 0.61; P < .00001). PBSCT was associated with a significant increase in the development of grade 3-4 acute graft-versus-host disease (GVHD; OR = 1.39; 95% CI, 1.03 to 1.88) and extensive (47% v 31% at 3 years; OR = 1.89; 95% CI, 1.47 to 2.42; P < .000001) and overall chronic GVHD (68% v 52% at 3 years; OR = 1.92; 95% CI, 1.47 to 2.49; P < .000001), but not grade 2-4 acute GVHD (54% v 53%; P = .49). PBSCT was associated with a decrease in relapse (21% v 27% at 3 years; OR = 0.71; 95% CI, 0.54 to 0.93; P = .01) in both late-stage-(33% v 51% at 3 years; OR = 0.59; 95% CI, 0.38 to 0.93; P = .02) and early-stage-disease patients (16% v 20% at 3 years; OR = 0.69; 95% CI, 0.49 to 0.98; P = .04). Nonrelapse mortality was not different between groups. Overall and disease-free survival were only statistically significantly improved in patients with late-stage disease (overall survival: 46% v 31% at 3 years; OR = 0.64; 95% CI, 0.46 to 0.90; P = .01; disease-free survival: 41% v 27% at 3 years; OR = 0.63 95% CI, 0.45 to 0.87; P = .01). CONCLUSION: PBSCT is associated with a decreased relapse rate in hematologic malignancies and improvement in overall and disease-free survival in patients with late-stage disease. PBSCT is also associated with a significant risk of extensive chronic GVHD.